Characterization and properties of BaTi3O3/MgO nanocomposite ceramics - Vittayakorn W.C. (2014)
In this research, BaTiO3./xMgO nanocomposite ceramics, where x = 0, 0.3, 0.5, 0.7 and 1.0 vol%, were prepared by a mixedoxide method. The effect of MgO additions on the phase formation, microstructure and dielectric properties of this system was investigated via X-ray diffraction (XRD), scanning electron microscopy (SEM) and dielectric spectroscopy, respectively. From the results, XRD analysis showed that there is no unwanted phase except BaTiO 3 and MgO observed in these ceramics. Abnormal grain growth was found in pure BaTiO3 ceramic with a 75.32 μm average grain size. After adding MgO nanoparticles into the system, the grain size significantly decreased to 0.55 μm and continuously decreased with increasing MgO content. For the dielectric properties, the pure BT ceramic exhibits a sharp and high dielectric peak whereas a low and broad peak is found in BT/MgO nanocomposite ceramics, which can be explained by the composite structure.